Accelerated aging for gate oxide of SiC MOSFETs under continuous switching conditions by applying advanced HTGB test. (November 2021) - Hayashi, Shin-Ichiro; Wada, Keiji
Abstract: Silicon carbide (SiC) metal-oxide-semiconductor–field-effect transistors (MOSFETs) are expected to be widely used for various applications, but there is a lack of long-term reliability data. Therefore, the long-term reliability should be evaluated under continuous switching conditions, as in the operation of an actual power conversion circuit. In this study, an accelerated aging test is performed under continuous switching conditions. In the accelerated aging test, the degradation of SiC MOSFETs can be accelerated at practical voltage and current ratings and switching frequencies. The accelerated aging test is performed for four types of SiC MOSFETs, including different gate structures. The results of these tests support the validity of the accelerated aging test. Highlights: An accelerated aging test circuit for power devices under continuous switching conditions has been developed. Accelerated aging tests were carried out on 4 types of SiC MOSFETs with different manufacturers and gate structures. On-resistance and gate threshold voltage fluctuations were observed in all 4 types of SiC MOSFETs. The proposed test circuit is effective for the development of condition monitoring technology of power devices.